Does the Higher School Philosophy Fulfil Its Function? - Černienė, Bronislava (Problemos, 1990)
The necessity has arisen to revise the philosophy which is taught at higher schools. It is necessary to eliminate the various relicts of dogmatism as well as the positivistic technocratic tendencies in it. Also the relations between thinking and practice, objective and subjective, gnoseology and axiology must be reviewed. The landmark of the reconstruction in philosophy must become the idea of humanism.